Impact of Physician Densities on Gynecologic Cancer Outcomes in the United States [A316]. (May 2022) - Smick, Alexandra H.; Neff, Robert; Holbert, Michael
Abstract : INTRODUCTION: To examine the relationship between county-level obstetrician-gynecologist (GYN) and primary care physician (PCP) densities and gynecologic cancer outcomes and whether county socioeconomic factors affect cancer prognosis. METHODS: An analysis of gynecologic cancers (uterine, ovarian, cervical) in the Surveillance, Epidemiology, and End Results (SEER) database was performed from 2005 to 2018. County-level demographics were abstracted from SEER, population density from the U.S. Census, and physician density (GYN and PCP per 100, 000 females) from the Area Health Resources File. PCP included family, internal, and general medicine physicians. Backward stepwise regression models were used. RESULTS: Final analysis included 120, 000 patients from the SEER database comprised of those with cervical (14.4%), uterine (60.2%), and ovarian cancers (25.4%). Initial analysis included 620 U.S. counties (41% metropolitan, 59% nonmetropolitan). Mean GYN density was 12 per 100, 000 females and mean PCP density was 99 per 100, 000 females. Multivariate analysis for cancer stage by primary site showed that GYN density was inversely correlated with cancer stage at diagnosis ( P =.001). Analysis also showed that percent Black population was positively correlated with cancer stage ( P =.001), whereas household income was negatively correlated with cancer stage ( P =.01). Multivariate analysis for 5-year survival by cancer stage showed no correlation with GYN or PCP density. We found that educational attainment ( P =.01) and population size ( P =.001) were positively correlated with 5-year survival ( P =.01). CONCLUSION: Lower GYN density was associated with more advanced cancer stage at time of diagnosis across the United States. Nonmetropolitan county status was also associated with worse cancer outcomes. Targeting GYN physician supply in lower-density counties may help improve population-based gynecologic cancer care.